Nitrogen Metabolism and Biomass Production in Forest Trees - Cánovas, Francisco M.; Cañas, Rafael A.; de la Torre, Fernando N.; Pascual, María Belén; Castro-Rodríguez, Vanessa; Avila, Concepción (Frontiers in Plant Science, 2018)
Low nitrogen (N) availability is a major limiting factor for tree growth and development. N uptake, assimilation, storage and remobilization are key processes in the economy of this essential nutrient, and its efficient metabolic use largely determines vascular development, tree productivity and biomass production. Recently, advances have been made that improve our knowledge about the molecular regulation of acquisition, assimilation and internal recycling of N in forest trees. In poplar, a model tree widely used for molecular and functional studies, the biosynthesis of glutamine plays a central role in N metabolism, influencing multiple pathways both in primary and secondary metabolism. Moreover, the molecular regulation of glutamine biosynthesis is particularly relevant for accumulation of N reserves during dormancy and in N remobilization that takes place at the onset of the next growing season. The characterization of transgenic poplars overexpressing structural and regulatory genes involved in glutamine biosynthesis has provided insights into how glutamine metabolism may influence the N economy and biomass production in forest trees. Here, a general overview of this research topic is outlined, recent progress are analyzed and challenges for future research are discussed.